Audit Committee Effectiveness and Fraud Occurrence - Christine Novita Dewi; Gudono Gudono (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to examine the effect of audit committee effectiveness on the fraud occurrence within state-owned enterprises/BUMN. The study uses a Partial Least Square (PLS) based Structural Equation Model. The sample consists of thirty one state-owned companies (BUMN) – out of one hundred and fourty one BUMN which were actively operating in Indonesia during the period of 2007 – 2010 or about 22 percent of the existing BUMN. Samples were selected using the purposive sampling method.   The results show that audit committee effectiveness is negatively associated with fraud indications within BUMN. The more effective the audit committee, which is proxied by its members’ expertise, size and activeness of the audit committee in carrying out the role and duties, the fewer the indications of fraud.